2017
DOI: 10.1016/j.copsyc.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Mental toughness: progress and prospects

Abstract: Mental toughness (MT) has become a popular area of investigation and practice within sport and exercise psychology over the past two decades. Since the turn of the twenty first century, there have been hundreds of studies published on mental toughness, yet concerns remain about the conceptualisation and measurement of mental toughness. In this paper, I take stock of past work with the goal of clarifying and elaborating the most fundamental and common aspects of MT. I also look to the future and outline key sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 47 publications
5
93
0
12
Order By: Relevance
“…In line with recent conceptualisations, we define MT in this study as a psychological resource that enables athletes to initiate and sustain efforts towards goal-directed endeavours. 22,23 We acknowledge that researchers continue to debate the conceptualisation of MT and approaches to measurement. 22,24 For example, while some have produced models and measures that reflect a multidimensional, trait-like construct 25 , others have proposed MT to be unidimensional and state-like 22 .…”
Section: Perfectionism Mental Toughness and Motivationmentioning
confidence: 99%
“…In line with recent conceptualisations, we define MT in this study as a psychological resource that enables athletes to initiate and sustain efforts towards goal-directed endeavours. 22,23 We acknowledge that researchers continue to debate the conceptualisation of MT and approaches to measurement. 22,24 For example, while some have produced models and measures that reflect a multidimensional, trait-like construct 25 , others have proposed MT to be unidimensional and state-like 22 .…”
Section: Perfectionism Mental Toughness and Motivationmentioning
confidence: 99%
“…This finding is noteworthy given that Clough et al added confidence to the hardiness construct (Kobasa, 1979) in order to conceptualise their model of MT. Therefore, Clough et al's extension of the hardiness construct may not be as theoretically important as the other hardiness components (Gucciardi, 2017). Interestingly, the confidence subscales rotated with the least amount of misspecification in the overall sample.…”
Section: Parameter Estimates For Invariance Measurement Modelsmentioning
confidence: 99%
“…It is theorised that this emphasis resulted in less attention being given to measurement, that is, a lack of rigorous psychometric evaluation via quantitative methods (Crust & Swann, 2011). Furthermore, a recent analysis of this work has highlighted insufficient distinctiveness of Clough et al's conceptualisation, that is, whether the 4Cs model of MT is a distinct concept, or an extension of hardiness, thus clouding the uniqueness and operationalisation of the model (Gucciardi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mental toughness (MT) has been shown to be a prerequisite for success in many competitive sports (Gucciardi, 2017). Evidence has found that mental toughness distinguishes athletes at different levels within sports, such as Mixed Martial Arts (Chen & Cheesman, 2013) and Australian Football (Gucciardi, Gordan & Dimmock, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics such as problem focused coping (Nicholls, et al, 2011) and self-belief (Chen & Cheesman, 2013) have been found to be related to mental toughness. Mental toughness can be defined as a state-like psychological resource that is purposeful, flexible and efficient for the enactment and maintenance of goal directed pursuits (Gucciardi, 2017). A central facet of this model, is that MT is a state like resource (Brand, et al, 2014) and a key element of self-regulation in response to losing.…”
Section: Introductionmentioning
confidence: 99%